Law Enforcement of the Police Security Intelligence Unit in Uncovering Criminal Acts in the Buleleng Resort Police Area - Simpen, I Nengah; Sihotang, Erikson; Sihotang, I Nyoman (CV. Syntax Corporation Indonesia, 2025)
The main tasks and functions of Intelkam in the Polri environment are regulated by the Regulation of the Chief of the Republic of Indonesia National Police Number 22 of 2010 concerning the Organizational Structure and Work Procedures at the Regional Police Level and the Regulation of the Chief of the Republic of Indonesia National Police Number 23 of 2010 concerning the Organizational Structure and Work Procedures at the Resort Police and Sector Police Levels. Law Enforcement by the Police Intelligence Unit In uncovering criminal acts in the Buleleng Resort Police Area According to Law Number 2 of 2002 concerning the Indonesian National Police, the role and duties of the Buleleng Police intelligence unit are to search for and uncover criminal acts in order to reveal who committed the crime, so that the perpetrators can be sentenced in accordance with the Criminal Code. The obstacles faced by the police security intelligence unit in enforcing criminal law in order to uncover criminal acts in the Buleleng Resort Police area are in the form of internal obstacles within the police themselves and external obstacles. Internal obstacles are related to the quality of human resources of the police and external obstacles in the form of the community and related institutions not being able to cooperate in enforcing the law.